A randomized phase II study of gemcitabine plus Z-360, a CCK2 receptor-selective antagonist, in patients with metastatic pancreatic cancer as compared with gemcitabine plus placebo - Ueno, Makoto (Cancer Chemother Pharmacol, 2017)
BACKGROUND: We investigated the efficacy and safety of 60, 120, or 240 mg of Z-360, which is a highly potent cholecystokinin2-receptor-selective antagonist, combined with gemcitabine in patients with metastatic pancreatic cancer. METHODS: Patients were randomly assigned in a 1:1:1:1 ratio to one of four treatment groups. Patients received 1000 mg/m(2) gemcitabine for each cycle and Z-360 tablets of 60 mg (GZ 60 mg group), 120, 240 mg or placebo tablets (Gem group) orally twice daily. The primary endpoint was overall survival (OS). RESULTS: The median OS was 1.3 months longer in the GZ 60 mg group compared with the Gem group (8.5 vs. 7.2 months) and the risk of death was reduced by 19% compared with the Gem group, although there were no statistically significant differences. The study treatments were well tolerated. CONCLUSIONS: In this Phase II study, no statistically significant differences between the GZ groups and Gem group were detected in any analysis. However, Z-360 in dose of 60 mg tends to improve OS in patients with metastatic pancreatic cancer with low toxic effect. Further exploratory trials with other agents such as gemcitabine plus nab-paclitaxel might be beneficial. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00280-017-3351-4) contains supplementary material, which is available to authorized users.